2012
DOI: 10.1007/s00214-012-1171-5
|View full text |Cite
|
Sign up to set email alerts
|

Decomplexation and complexation of alkali metal cations by a crown-ether-type podand in dichloromethane: a steered molecular dynamics study

Abstract: The decomposition of three complexes involving the alkali metal cations Li ? , Na ? and K ? and a potentially octadentate polyethylene-glycol-type podand(1,2-bis-{2-[2-(2-methoxy-ethoxy)-ethoxy]-ethoxy}-benzene, hereafter b33) in dichloromethane was studied by steered molecular dynamics (SMD). This technique proved applicable to the problem. Analysis of the resulting trajectories allowed phenomenological descriptions of the decomposition processes. Use of the Jarzynski identity allowed the estimation of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Our observations of the magnitude of hydration and the consistent partial loss of the second solvation shell are in excellent agreement with prior studies; dos Santos and Gomes report cesium and Chorny and Benjamin report sodium losing comparable amounts of its second solvation shell when entering nitrobenzene, but they report persistent first shell hydration. Furthermore, refs and discuss similar water wedge formation and encapsulation of cation K + at the water–dichloromethane interface.…”
Section: Discussionmentioning
confidence: 89%
“…Our observations of the magnitude of hydration and the consistent partial loss of the second solvation shell are in excellent agreement with prior studies; dos Santos and Gomes report cesium and Chorny and Benjamin report sodium losing comparable amounts of its second solvation shell when entering nitrobenzene, but they report persistent first shell hydration. Furthermore, refs and discuss similar water wedge formation and encapsulation of cation K + at the water–dichloromethane interface.…”
Section: Discussionmentioning
confidence: 89%
“…Valente et al. showed that H 2 O will initially cross the interface as a water droplet around the cation, before returning to the bulk H 2 O phase on the order of 1–2 ns . Based on this time scale relative to the time scale for experimental extraction, we could confidently conclude all superfluous H 2 O molecules will dissipate prior to selectivity measurements.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent MD study by Valente et al. in 2012 used a custom crown ether in dichloromethane solvent to calculate the binding free energies of lithium, sodium, and potassium . They found that the selectivity of their crown ethers to alkali metals increased with decreasing ionic radius.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent binding properties of biological receptors are still assigned to self-assembly, molecular recognition and multivalency. Multiple-interaction ligands are useful both for cation binding and protein surface recognition, cell transfection or crystal engineering [ 1 5 ]. All these many possibilities are associated also with a wide panel of scaffolds used for the synthesis of modern podands.…”
Section: Introductionmentioning
confidence: 99%